Archival classification: new usage scenarios among semantic web and traditio of digital samples - Alessandro Alfier (JLIS.it, 2017)
Starting from the acknowledgement of the basic purpose assigned by tradition to classification within documents management, the article faces the issues related to new needs and usage, related to the digital scenarios, that would allow classification to consolidate its tradition of effectiveness in a new digital environment. The key point of the article is represented by the in-depth analysis of the possible synergies between classification-related activities and the International Standard for Describing Functions (ISDF), developed by ICA in 2007. The article highlights how an approach to classification elaborated from the ISDF perspective allows classification itself to enrich from purposes and semantic web related usage, and with the traditio of digital documents.